Work-related musculoskeletal disorder and health risk behaviors in market-vendors: a mixed-methods study - Cetthakrikul, Salila; Perngparn, Usaneya (PeerJ, 2024)
Background Work-related musculoskeletal disorders (WRMDs) are frequently observed among market vendors, and engaging in health risk behaviors can exacerbate these issues, leading to various health problems. Common health risk behaviors among market vendors include alcohol consumption and insufficient physical activity. However, there is currently a lack of research examining the prevalence of WRMDs and health risk behaviors among market vendors in Bangkok. Furthermore, the emerging trend of drug misuse within this group remains poorly understood. This study aims to explore the prevalence of muscle pain and flexibility issues and assess health risk behaviors, including alcohol consumption, inadequate exercise, and drug misuse, among market vendors. Methods A mixed-method study was undertaken among 213 market vendors in Bangkok. Data collection utilized direct observation techniques, questionnaires, and muscle flexibility tests. Qualitative data were elucidated and showcased through textual descriptions and quotations. Quantitative data were analyzed using descriptive statistics to present numerical and percentage values. Results Qualitative findings revealed that market vendors often engage in static muscular work and maintain awkward postures due to their job characteristics and workstation setups. Quantitatively, the right arm was the most common pain region (34.7%), followed by the left leg (31.0%), right leg (30.0%), and left arm (28.6%). Additionally, 64.3% of participants showed poor muscle flexibility. The study also found that 35% of market vendors resorted to alcohol and 11.7% to drug misuse to cope with fatigue and prevent adverse symptoms. Moreover, 68.5% of participants reported no regular exercise due to lack of time. Conclusion The study highlights the prevalence of musculoskeletal issues among market vendors, largely attributed to static muscular work and awkward postures dictated by their job roles and workstation arrangements. The right arm emerged as the most commonly affected area, followed by the left leg, right leg, and left arm, with significant rates of reported pain. The research also points to a notable lack of muscle flexibility in a majority of vendors and a concerning tendency towards alcohol and drug misuse as coping mechanisms for fatigue and symptom management. Furthermore, a significant portion of the vendors do not participate in regular exercise, primarily due to time constraints. These findings can be used to implement health prevention programs within the market vendor group.
Keywords: Work-related musculoskeletal disorders; Health risk behaviors; Market-vendors; Muscle pain; Alcohol consumption; Drug misuse; Muscle flexibility; Physical inactivity